PENGELOLAAN BUDAYA SEKOLAH DI SMK TIARA AKSARA - Komariah; Latifah, Siti; Sulastri; Hafni, Syarifah; Hasanah, Yenny Marinatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of effective school management as the foundation for establishing a positive and high-quality school culture at SMK Tiara Aksara, Tangerang City. A qualitative descriptive approach was employed, utilizing observation, interviews, and documentation as data collection techniques through the School Field Introduction Program (PLP). The findings indicate that effective school management is reflected in the development of a religious, disciplined, and character-oriented school culture. Furthermore, the availability and proper management of educational facilities and infrastructure, active and innovative learning processes, and well-organized co-curricular and extracurricular programs contribute significantly to creating a conducive learning environment. The leadership of the principal, collaboration among school stakeholders, and the active involvement of the foundation serve as key factors in fostering a positive school culture. The study concludes that effective school management plays a crucial role in improving the quality of educational services and strengthening students’ character development. Therefore, effective school management can serve as a strategic approach to achieving sustainable educational quality and cultivating a positive school culture.